CAFTA and U.S. Sugar - Andrew Schmitz; Troy G. Schmitz; James L. Seale, Jr. (EDIS)
The Central American Free Trade Agreement (CAFTA) is a trade agreement between the United States and Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua, and the Dominican Republic. The agreement was put into law in 2005. Under the agreement the Dominican Republic will eliminate their sugar tariffs over a 15-year period. The United States will establish additional tariff rate quotas (TRQs) for the CAFTA countries beginning with an additional 107,000 metric tons in the first year. The quota amount increases to 151,140 metric tons by the end of the 15-year period. The United States is allowed to compensate exporters in an effort to limit sugar imports for stock management purposes. How large of an impact will CAFTA have on U.S. sugar producers? This document is FE578, one of a series of the Food and Resource Economics Department, UF/IFAS Extension. Original publication date January 2006.